HUBUNGAN PERAN ORANG TUA DENGAN PERKEMBANGAN KOGNITIF ANAK PRASEKOLAH DI TK ISLAM AL-HUDA SANGKAPURA - Sitti Navia; Ernawati (Rena Cipta Mandiri, 2025)
Children's cognitive development is greatly influenced by the role of parents. If parents provide stimulation to children from an early age, then the child's development, including cognitive development, will have a positive impact in the future. The aim of the research was to determine the relationship between the role of parents and the cognitive development of preschool children at Al-Huda Sangkapura Islamic Kindergarten. This research is a correlational analytic with a cross sectional approach. The population in this study was 46 preschool children. The sample in this study was the entire population, namely preschool children using a total population sampling technique. Data analysis used the Spearman Rank test, the research instrument used a questionnaire on the role of parents and the cognitive development of preschool children. The results of the study show that the role of parents is adequate at 26. The cognitive development of children aged 4-5 years is starting to develop at 12 and at the age of 5-6 years is developing very well at 11. Spearman rank test analysis of the relationship between the role of parents and cognitive development at age 4 -5 years with a p value of 0.005 > α, 0.05 aged 5-6 years with a p value of 0.014 > α 0.05.There is a relationship between the role of parents and the cognitive development of preschool children at Al-Huda Sangkapura Islamic Kindergarten., It is hoped that parents must play a more active role in children's development.